Arsenic-induced plant growth of arsenic-hyperaccumulator Pteris vittata: Impact of arsenic and phosphate rock. (April 2016) - Han, Yong-He; Yang, Guang-Mei; Fu, Jing-Wei; Guan, Dong-Xing; Chen, Yanshan; Ma, Lena Q.
Abstract: Phosphate rock (PR) has been shown to promote plant growth and arsenic (As) uptake by As-hyperaccumulator Pteris vittata (PV). However, little is known about its behaviors in agricultural soils. In this study, impact of 50 mg kg −1 As and/or 1.5% PR amendment on plant As accumulation and growth was investigated by growing PV for 90 d in three agricultural soils. While As amendment significantly increased plant As uptake and substantially promoted PV growth, the opposite was observed with PR amendment. Arsenic amendment increased plant frond As from 16.9–265 to 961–6017 mg kg −1, whereas PR amendment lowered frond As to 10.2–216 mg kg −1 . The As-induced plant growth stimulation was 69–71%. While PR amendment increased plant Ca and P uptake, As amendment showed opposite results. The PV biomass was highly correlated with plant As at r  = 0.82, but with weak correlations with plant Ca or P at r  < 0.30. This study confirmed that 1) As significantly promoted PV growth, probably independent of Ca or P uptake, 2) PR amendment didn't enhance plant growth or As uptake by PV in agricultural soils with adequate available P, and 3) PV effluxed arsenite (AsIII) growing in agricultural soils. Graphical abstract: Highlights: Arsenic amendment increased As uptake and plant growth of Pteris vittata (PV). Phosphate rock (PR) amendment decreased As uptake and plant growth of PV. PR promoted but As decreased Ca and P uptake by PV. PV growth was strongly correlated with plant As with r  = 0.82. 9–15% arsenite was detected in control soils after PV growth.